Chasing breeding footprints through structural variations in Cucumis melo and wild relatives. Issue 1 (22nd December 2020) - Demirci, Sevgin; Fuentes, Roven Rommel; Dooijeweert, Willem van; Aflitos, Saulo; Schijlen, Elio; Hesselink, Thamara; de Ridder, Dick; Dijk, Aalt D J van; Peters, Sander
Abstract: Cucumis melo (melon or muskmelon) is an important crop in the family of the Cucurbitaceae. Melon is cross pollinated and domesticated at several locations throughout the breeding history, resulting in highly diverse genetic structure in the germplasm. Yet, the relations among the groups and cultivars are still incomplete. We shed light on the melonbreeding history, analyzing structural variations ranging from 50 bp up to 100 kb, identified from whole genome sequences of 100 selected melon accessions and wild relatives. Phylogenetic trees based on SV types completely resolve cultivars and wild accessions into two monophyletic groups and clustering of cultivars largely correlates with their geographic origin. Taking into account morphology, we found six mis-categorized cultivars. Unique inversions are more often shared between cultivars, carrying advantageous genes and do not directly originate from wild species. Approximately 60% of the inversion breaks carry a long poly A/T motif, and following observations in other plant species, suggest that inversions in melon likely resulted from meiotic recombination events. We show that resistance genes in the linkage V region are expanded in the cultivar genomes compared to wild relatives. Furthermore, particular agronomic traits such as fruit ripening, fragrance, and stress response are specifically selected for in the melon subspecies. These results represent distinctive footprints of selective breeding that shaped today's melon. The sequences and genomic relations between land races, wild relatives, and cultivars will serve the community to identify genetic diversity, optimize experimental designs, and enhance crop development.